Improvement of SCTP congestion control in the LTE-A network - Najm, I.A.; Ismail, M.; Lloret, J.; Ghafoor, K.Z.; Zaidan, B.B.; Rahem, A.A.R.T. (Elsevier, 2015)
Long Term Evolution-Advanced (LTE-A) is the fourth-generation wireless communication of mobile technology. LTE-A offers a scalable coverage as it possesses efficient throughput and ubiquitous connectivity. The congestion control of the LTE-A transport layer negatively influences the overall performance of the throughput. Moreover, the existing slow-start and congestion avoidance mechanisms helps to reduce the LTE-A performance. Thus, this paper improves the congestion control mechanism by incorporating the Stream Control Transmission Protocol (SLIP) in LTE-A. Specifically, the slow-start and congestion avoidance phases will be improved. The proposed mechanism, called ENH-SCTP, reduces the time duration, towards reaching a threshold, by ranking the congestion window, throughput, queue size and packet loss as performance metrics. The ranking can be achieved by adding a value which selection is based on a multi-criteria problem. Concretely we used the multi-criteria decision-making (MCDM) technique, especially the utilization of the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). The simulation results show that the proposed SCTP in LTE-A performs better than the conventional SCTP. As a consequence, the congestion window, throughput, queue size and packet loss are significantly improved. (C) 2015 Elsevier Ltd. All rights reserved.